Q&A - Ask Doubts and Get Answers
Q

Factorise : (iii) 6x ^2 + 5x - 6

4.(iii)  Factorise :

    (iii)    6x^2 +5x - 6

Answers (1)
Views

Given polynomial is   6x^2 +5x - 6

We need to factorise the middle term into two terms such that their product is equal to 6 \times -6 =-3 6 and their sum is equal to 5

We can solve it as 

\Rightarrow 6x^2 +5x - 6

\Rightarrow 6x^2 +9x -4x - 6                                       (\because 9 \times -4 = -36 \ \ and \ \ 9+(-4) = 5)

\Rightarrow 3x(2x+3)-2(2x+3)

\Rightarrow (2x+3)(3x-2)                             

Exams
Articles
Questions